Over Kapasitas Lembaga Pemasyarakatan Dalam Perespektif Kebijakan Hukum Pidana - Usman Usman; Bahder Johan Nasution; Elizabeth Seregar (Wajah Hukum, 2020)
Overcapacity of correctional institutions is a serious problem in realizing the objectives of the criminal justice system. This article seeks to identify the causes of overcapacity in prisons and formulate models of criminal law policies that can suppress the overcapacity of correctional institutions in Indonesia. Overcapacity of prisons is caused by: first, the high crime rate and limited prison facilities. Second, over criminalization criminal law policies that are not supported by alternative sanction crimes; easy requirements for detention and length of detention period, and restrictions on the provision of remissions. An integrated approach is needed in reducing overcapacity of prisons through criminal law and social policies, namely the fulfillment of detention facilities in prisons / detention centers and reducing the crime rate. In criminal law policy, decriminalization and depenalization are necessary for certain types of criminal acts to strengthen alternative crimes from imprisonment.